The study of public administration in perspective: a passing review of the development of the discipline - Reyes, Danilo R. (1995)
Public administration can be roughly defined as the implementation of public policy, largely by the executive branch. It can also be stated as a field of study preparing persons for careers in the public service. It has been said all through the years that Public Administration as a field of study evolved from Political Science, more of a stem from the branch. Apart from adopting theories from the social sciences, it has also embraced some schools of thought from the field of behavioral sciences. This paper discusses how Public Administration developed as a field of study by amalgamating principles from the other disciplines to eventually contrive its own foundations
Keywords: Public administration - Philippines; Public administration